Norwegian fathers' experiences with a home visiting program. Issue 1 (22nd October 2021) - Solberg, Beate; Glavin, Kari; Berg, Rigmor C.; Olsvold, Nina
Abstract: Objective: To explore fathers' experiences with a Norwegian home visiting program during the prenatal period and the first‐year postpartum. Design: Qualitative design with interpretive description (ID) as the methodological approach. Sample: Individual interviews with fathers ( n  = 13) who received home visits by a public health nurse (PHN) within the New Families home visiting program. Measures: Interviews were guided by a semi‐structured interview‐guide, which contained open‐ended questions encouraging informants to reflect on their experiences with home visits. The analysis of the data was informed by content analysis. Results: Two main themes that reflect the fathers' experiences emerged: (1) The importance of being on their home ground captures the fathers' experience of receiving home visits and building a trusting relationship with the PHN. (2) Including fathers in the home visit represents their thoughts about the content and focus of the home visits. Conclusions: Fathers experienced the universal New Families home visiting program as an important contribution towards a more available and tailored service, with the home environment as a suitable arena for developing a trusting relationship with the PHN. However, the fathers often felt insufficiently included in the home visits, with only scant attention towards them as independent caregivers, their emotional reactions, roles, and family relationships. Pre‐birth home visits might contribute to strengthening preparations for fatherhood and increase fathers' engagement in the Child Health Service.